(untitled) (Scientific journal of the Fergana State University, 2024)
The differences in the speech of individuals from various societies due to factors such as race, gender, age, social status, appearance, and health conditions (disabilities), among others. In scientific studies dedicated to the problem of male and female speech in global linguistics, these speech concepts are defined differently, such as linguistic style, linguistic variant, and linguistic diversity. Male and female speech represents a specific social distinction and exhibits its characteristics within different styles.